Strategi Peningkatan Aktivitas Bisnis Di Kawasan Bisnis Mmtc Pancing Medan - Nirwaty Tarigan (Akademi Pariwisata Darma Agung, 2018)
Business activity in the MMTC Pancing not as expected. With a wide range of facilities that are expected as an appeal to the people or consumers to visit this region, but the condition of the opposite happened. Many shop are not yet in operation, so the business district is still quiet. Various policies have made the company, yet provide optimal results, so we need the right strategy by considering the internal environment and external environment MMTC Pancing. The purpose of this research is to formulate a strategy in order to increase business activity in the shop that sold in the business district MMTC Pancing. This type of research in this study is action research, with the data analysis SWOT analysis. The results of the data analysis resulted in the diversification strategy of the strategy pursued by forming various types of business or activities that are related or not related to each other to increase business activity in the MMTC Pancing